1974
DOI: 10.1111/j.1464-410x.1974.tb03828.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of the Adult Urinary Stone Problem in Great Britain and Northern Ireland

Abstract: Summary In a collection of 856 urinary calculi from Great Britain and Northern Ireland, the most abundant and frequently occurring crystalline constituents are the mono‐ and di‐hydrates of calcium oxalate and hydroxy‐ and carbonate‐apatite. On the basis of composition, most stones can be assigned to a few well‐defined groups. The most common composition type, accounting for 34% of the collection, is that composed of calcium oxalate+calcium phosphate. The oxalate can be either or both of the hydrates, often bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…For instance. Sutor et al [15] found 6.9% of stones to be 'pure' calcium phosphate and this could account for the higher frequency that we found using the criterion of an 0:P ratio of < 1:1. Fig.…”
Section: Frequency Of Calcium Phosphate Stonesmentioning
confidence: 49%
See 1 more Smart Citation
“…For instance. Sutor et al [15] found 6.9% of stones to be 'pure' calcium phosphate and this could account for the higher frequency that we found using the criterion of an 0:P ratio of < 1:1. Fig.…”
Section: Frequency Of Calcium Phosphate Stonesmentioning
confidence: 49%
“…Sutor et al [15] found a relatively greater proportion of females among patients with mixed calcium oxalate and phosphate stones, compared with calcium oxalate stones, but only if the patients were 50 years or less. In one of the few studies in which quantification of the amounts of oxalate and phosphate has been related to sex, Otnes [17] found that 43% of 44 patients with stones containing 50% or more calcium phosphate (excluding those with MAP) were females; however, only 25% of 198 patients with stones containing more than 50% calcium oxalate, were females.…”
Section: Sex and Urolithiasismentioning
confidence: 99%
“…11 The explanation for the presence of bacteria within the calculi may be due to insignificant intermittent bacteriemia, from where the bacteria are excreted in renal pelvis and may act as a nidus for deposition of crystals either by damaging the mucous coat or perhaps also by acting as a nidus for crystallization of salts. 12 Thus, a vicious cycle starts, the infection leading to stone formation and then the stone causing infection. 13 Most of the current literature on the subject focuses on pathogenesis of infectious urinary stones.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients present recurrent kidney stones and metabolic disorders (5-7). Male patients predominate, but about 30% of patients are female (1)(2)(3).…”
Section: Is Nephrolithiasis a Matter Of Imbalances In Mineral Metabolmentioning
confidence: 99%
“…Nephrolithiasis (or kidney stones) is one of the most common diseases in countries like the USA, United Kingdom, Japan, and Brazil (1)(2)(3)(4). Most of the patients present recurrent kidney stones and metabolic disorders (5-7).…”
Section: Is Nephrolithiasis a Matter Of Imbalances In Mineral Metabolmentioning
confidence: 99%